Efficacy and safety of arterial blood gas analysis via distal radial artery in children - Yang, Ling; Ding, Heng; Zhou, Xiaoting; Shu, Shiting; Mao, Wenjie; Cai, Gaojun; Zhao, Yidong; Wan, Yu; Huang, Zhiying (Frontiers in Pediatrics, 2025)
ObjectiveThe distal transradial approach is widely accepted in adult cardiovascular interventions and invasive arterial blood pressure monitoring. However, limited evidence exists regarding the efficacy and safety of arterial blood gas analysis (ABGA) via the distal radial artery (DRA) in children.MethodsThis retrospective study evaluated the efficacy and safety of arterial puncture via the DRA compared with the conventional radial artery (CRA) for ABGA in children.ResultsA total of 240 children were allocated to either the DRA group (n = 140) or the CRA group (n = 100). The success rate (82.1% vs. 92.0%, p = 0.029) and one-needle success rate (75.7% vs. 89.0%, p = 0.009) were significantly lower in the DRA group. Puncture time in the DRA group was significantly longer than that in the CRA group, whereas hemostasis time was shorter in the DRA group. The incidences of incorrect venipuncture (11.4% vs. 1.0%, p = 0.002) and thumb numbness (5.7% vs. 0.0%, p = 0.022) in the DRA group were significantly higher than those in the CRA group. However, the incidence of hematoma (modified EASY Ia type) in the DRA group was significantly lower than that in the CRA group (8.6% vs. 50.0%, p < 0.001). No significant differences were observed in the incidences of hemorrhage or radial artery occlusion between the two groups.ConclusionDRA puncture for ABGA in children appears to be a safe and practical alternative to CRA. Although first-attempt success is slightly lower and training is required, the reduced risk of hematoma and shorter hemostasis time make it a promising option for clinical use.